HYPNOSIS COMMUNICATION PATTERNS IN BUILDING CLIENT SELF-AWARENESS AND MENTAL HEALTH - Tarsani; Yoedo Shambodo; Fachmi Ibrahim; Risqi Inayah Dwijayanti; Radita Gora Tayibnapis (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The changes and pressures of daily life often leave people feeling bored and stressed, making it difficult to maintain a healthy mindset. Various illnesses arise from human negligence, such as not maintaining a healthy lifestyle, or are caused by viral, bacterial, and other factors that disrupt physical health. However, beyond these factors, there are also non-medical causes of bodily "illness," namely disorders arising from mental and emotional conditions, as well as the accumulation of subconscious thoughts known as psychosomatics. One method that can be used to help recover from these conditions is hypnotherapy, the application of hypnosis techniques for therapeutic purposes. This study aims to analyze communication patterns in the hypnosis process, which play a role in fostering self-awareness and improving the client's mental health. The research approach used qualitative methods through in-depth interviews, observations, and document reviews. Data were analyzed to identify effective hypnotic communication patterns that enable suggestions to be accepted by the client's subconscious mind. The results provide insight into hypnosis techniques used in therapy and communication strategies that therapists can use effectively. The client's determination to recover, maintaining a positive mindset, and maintaining mental health are crucial factors in achieving their life goals. Selecting appropriate communication techniques and strategies helps therapists determine the appropriate approach to addressing client issues. This research emphasizes the importance of therapists' sensitivity in recognizing clients' capacities and resources so that communication can improve their self-awareness and mental health.